1983
DOI: 10.1093/infdis/148.1.101
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Human Alveolar Macrophages on the Bactericidal Capacity of Neutrophils

Abstract: Human alveolar macrophages (AMs) were obtained by bronchoscopy from 11 healthy adult subjects and placed into tissue culture for 24 hr. Brief preexposure (15 min) of human neutrophils to AM culture supernatants led to a greater than twofold increase in neutrophil killing of a serum-resistant strain of Pseudomonas aeruginosa (P less than 0.02). No increase in phagocytosis of 35S-labeled Pseudomonas could be detected for neutrophils preexposed to AM supernatants. However, upon exposure to bacteria, neutrophils p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Initial studies using the eight newly generated human AM culture specimens confirmed our previous observation (5). Neutrophils preexposed to supernatants from 24-h AM cultures reduced numbers of viable Pseudomonas by 3.01±0.33 (log1o) during 120-min incubations, while a mean decrease (log1o) of 2.13±0.27 was noted for neutrophils preexposed to medium only (P < 0.02).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Initial studies using the eight newly generated human AM culture specimens confirmed our previous observation (5). Neutrophils preexposed to supernatants from 24-h AM cultures reduced numbers of viable Pseudomonas by 3.01±0.33 (log1o) during 120-min incubations, while a mean decrease (log1o) of 2.13±0.27 was noted for neutrophils preexposed to medium only (P < 0.02).…”
Section: Resultssupporting
confidence: 80%
“…Abbreviations used in this paper: AM, alveolar macrophages; cfu, colony-forming units; f-met-leu-phe, formyl-methionyl-leucyl-phenylalanine; GBSS, Gey's balanced salt solution; HIFBS, heat-inactivated fetal bovine serum; IL-l, interleukin-l; LTB4, leukotriene B4; NAF, neutrophil-activating factor; NANA, N-acetylneuraminic acid; PMA, phorbol myristate acetate; SOD, superoxide dismutase. human AM contain material that, upon ekposure to neutrophils, enhances bactericidal activity of neutrophils (5). Neutrophils incubated with these supernatants demonstrated an increased respiratory burst during subsequent phagocytic challenge, an effect that was not related to increased phagocytic rates among the supernatant-exposed neutrophils.…”
Section: Introductionmentioning
confidence: 91%
“…Previous studies have shown that human mononuclear leucocytes stimu lated with phytohaemagglutinin release factors which enhance neutrophil-mediated killing of amoebae, tu mour cells, bacteria and fungi, and the capacity of neutrophils to damage cartilage [1][2][3][4]. Human macro phages also release mediators which enhance the tumourcidal [5] and bactericidal activity of neutrophils [6]. The mononuclear leucocyte-conditioned media rich in these activities also contained the capacity to stimulate an oxygen-dependent respiratory burst in the neutrophil [1,3,6], Indeed, some highly purified cytokines produced bv lymphocytes and macro phages or their recombinant counterparts have been shown to stimulate tumourcidal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages release numerous chemotaxins which include leukotriene B4 (LTB4) [23][24][25], plate let-activating factor (PAF) [26], tumour necrosis fac tor (TNF) [27], C5a [28], platelet-derived growth fac tor [29] and a 10,000 molecular weight molecule that has yet to be characterized fully [30]. Furthermore, macrophages secrete a 6,000-dalton glycoprotein (pi 7.6) which enhances the bactericidal activity of PMN [31,32], Peripheral blood MNC also secrete a range of pro-inflammatory cytokines with granulo cyte-activating properties including interleukin-1 (IL-1), TNF, colony-stimulating factors (CSFs) and hista mine-releasing factors (HRFs) [33][34][35][36]. They also se crete a range of heat-stable factors of heterogeneous size and charge which prime eosinophils and neutro phils for enhanced leukotriene generation following subsequent stimulation with A23187 [37], and factors including eosinophil cytotoxicity-enhancing factor, which prime eosinophils for enhanced cytotoxicity against schistosomula [38][39][40].…”
Section: Interactions Between Monocytes Macrophages and Granulocytesmentioning
confidence: 99%